Socialization of Natural Disaster Mitigation to Minimize the Impact of the Risk of Economic Loss in the Citarum River Basin (DAS) West Bandung Regency - Ade Kirana; Sani Sufyan Bature (Research Collaboration Community (RCC), 2022)
Flood is the flow of water at the ground surface that is relatively high and cannot be accommodated by drainage canals or rivers, causing inundation in an amount that exceeds normal and causes harm to humans. This flood disaster usually occurs in the lowlands around rivers, especially rivers that have various environmental problems such as factory waste, plastic waste, soil erosion, and so on. One of the rivers that often experience these flood events is the Citarum River, where the river has the title of the dirtiest river in the world. In order to reduce the impact caused by flooding, a Real Work Lecture (KKN) program was held by conducting community service regarding natural disaster mitigation training as an effort to minimize the impact of the risk of economic loss in the Citarum River basin, West Bandung Regency. The program is aimed at SMPN 1 CIhampelas students who are geographically close to the Citarum watershed. The method used is materialization regarding environmental problems in the Citarum watershed, the causes, and effects of flooding and its prevention, and disaster mitigation carried out when a flood occurs. After conducting the materialization, students were asked to discuss and explain how to mitigate floods when they occur at the school. Based on the results of the materials and tests carried out, it was found that students succeeded in conducting presentations on flood disaster mitigation, understanding the causes and effects of floods and how to prevent them, and understanding the importance of preserving the environment, especially in the Citarum River basin.